PEIRCE’S VISUAL SEMIOTIC IN EMOTIONAL CORRELATION MESSAGE AT “I CHOOSE AQUA” TV ADS - Andreas James Darmawan; Made Arini Hanindharputri; Kadek Adi Putra Wijaya (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
In Charles Sanders Peirce's theory, visual semiotics is the thinking behind how the representative could present a message with a suitable object for the audience as an interpreter. This research is conducted to learn visualization as an object; that could represent emotional correlation in one of AQUA's advertisements, titled "Family is the Most Important for Me". The research team found out that the correlation message in these ads is far from the product category itself; as bottled mineral water, this brand should not be consumed by a one-year-old child. In addition, the research team got a visual jump into the scene and considered dissociation in advertising message continuity. This research utilizes qualitative methods that divide several visual scenes in the ads and apply them to visual semiotics, focusing on object segmentation that implies content, context, and form. Data was collected by literature study, discussion with field experts, collecting data through video and social media, and interviews with advertising agencies and related advertising producers. These data were studied and divided scene by scene, correlated with visual semiotics and discussion results, then re-discussed with advertising agencies and producers to be concluded—the research team enlightened by advertising agency strategy, which is shrewdly sublimed visual, emotional message as the semiotic comparison. Also, in terms of continuity, these ads are visualized by a mother acting to protect her child and then being metaphorized to the mother's passion for protecting her child, sublimed with how AQUA protects nature quality.